2020
DOI: 10.3389/fimmu.2020.614402
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the FcεRI Pathway as a Potential Strategy to Prevent Food-Induced Anaphylaxis

Abstract: Despite attempts to halt it, the prevalence of food allergy is increasing, and there is an unmet need for strategies to prevent morbidity and mortality from food-induced allergic reactions. There are no known medications that can prevent anaphylaxis, but several novel therapies show promise for the prevention of food-induced anaphylaxis through targeting of the high-affinity IgE receptor (FcϵRI) pathway. This pathway includes multiple candidate targets, including tyrosine kinases and the receptor itself. Small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Second, we did not test mast cell functions, but we note that precise characterization of ex vivo mast cell desensitization is a very difficult task. In addition, our analyses did not elucidate activation markers such as CD63 or CD203c, or the intracellular signals that induce basophil desensitization, although other researchers are accumulating findings through active scrutiny of human basophils ( 3 , 5 8 ). Moreover, we do not know the extent to which desensitization induced by exposure to subthreshold allergen is similar or related to that induced by high–dose allergen.…”
mentioning
confidence: 81%
“…Second, we did not test mast cell functions, but we note that precise characterization of ex vivo mast cell desensitization is a very difficult task. In addition, our analyses did not elucidate activation markers such as CD63 or CD203c, or the intracellular signals that induce basophil desensitization, although other researchers are accumulating findings through active scrutiny of human basophils ( 3 , 5 8 ). Moreover, we do not know the extent to which desensitization induced by exposure to subthreshold allergen is similar or related to that induced by high–dose allergen.…”
mentioning
confidence: 81%
“…FcεRI has been targeted for clinical benefits to inhibit or attenuate MC degranulation, and effective clinical approaches for suppressing IgE-dependent MC activation have emerged [ 51 , 52 ]. Omalizumab, a humanized anti-IgE monoclonal antibody that binds to the Cε3 domain of IgE, can prevent the binding of circulating IgE to FcεRI, is a common and preferred treatment (especially for chronic urticaria), and is effective against asthma [ 53 , 54 , 55 ].…”
Section: Fcεri: Therapeutic Potential and Benefitsmentioning
confidence: 99%
“…Regarding other antibody antagonism/antibody neutralization, ligelizumab is another potent humanized anti-IgE monoclonal antibody that binds to free IgE with a higher affinity than omalizumab. Ligelizumab binds to the C3 domain of IgE, but unlike omalizumab, it can also bind to IgE-bound to CD23, a low-affinity IgE receptor expressed on B cells [ 51 , 69 ]. In 2020, Gasser et al demonstrated the structural and mechanistic differences between ligelizumab and omalizumab, where they report epitope differences between the anti-IgE antibodies and indicate the differences contribute to their qualitatively distinct IgE-receptor inhibition profiles [ 69 ].…”
Section: Fcεri: Therapeutic Potential and Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, IL-4 and IL-13 inhibitors such as dupilumab have been used to treat anaphylaxis by inhibiting mast cell expansion. These biological agents may be adjuncts in difficult-to-treat patients with immediate hypersensitivity and anaphylaxis [ 115 , 116 ]. Further clinical trials are needed to determine whether these medicines and biologic agents can be successfully used to treat patients with COVID-19-vaccine-induced immediate hypersensitivity or anaphylaxis.…”
Section: Treatment and Prevention Strategies For Covid-19-vaccine-ind...mentioning
confidence: 99%